The hitman's bodyguard - Hughes, Patrick, (Director); Reynolds, Ryan; Jackson, Samuel L.; Oldman, Gary (Santa Monica, California : Lionsgate, 2017)
A top protection agent must guard the life of his mortal enemy, a notorious hitman.
Originally released as a motion picture in 2017.
Dolby digital surround, wide screen 1.85:1.
Features: Big action in a big world; feature commentary with director Patrick Hughes.
Ryan Reynolds, Samuel L. Jackson, Gary Oldman, Salma Hayek, Élodie Yung.
MPAA rating: R.
In English with optional Spanish subtitles.
Keywords: Bodyguards -- Drama; Assassins -- Drama; Action and adventure films; Fiction films; Feature films; Comedy films